Mild hyperthermia enhances sensitivity of gastric cancer cells to chemotherapy through reactive oxygen species–induced autophagic death - Ming-Chen Ba; Hui Long; Shu-Zhong Cui; Yuan-Feng Gong; Zhao-Fei Yan; Shuai Wang; Yin-Bing Wu (Tumor Biology)
Mild hyperthermia enhances anti-cancer effects of chemotherapy, but the precise biochemical mechanisms involved are not clear. This study was carried out to investigate whether mild hyperthermia sensitizes gastric cancer cells to chemotherapy through reactive oxygen species–induced autophagic death. In total, 20 BABL/c mice of MKN-45 human gastric cancer tumor model were divided into hyperthermia + chemotherapy group, hyperthermia group, chemotherapy group, N-acetyl-L-cysteine group, and mock group. Reactive oxygen species production and expression of autophagy-related genes Beclin1, LC3B, and mammalian target of rapamycin were determined. The relationships between tumor growth regression, expression of autophagy-related genes, and reactive oxygen species production were evaluated. Tumor size and wet weight of hyperthermia + chemotherapy group was significantly decreased relative to values from hyperthermia group, chemotherapy group, N-acetyl-L-cysteine group, and mock group ( F  = 6.92, p  < 0.01 and F  = 5.36, p  < 0.01, respectively). Reactive oxygen species production was significantly higher in hyperthermia + chemotherapy group than in hyperthermia, chemotherapy, and mock groups. The expression levels of Beclin1 and LC3B were significantly higher, while those of mammalian target of rapamycin were significantly lower in hyperthermia + chemotherapy group than in hyperthermia, chemotherapy, and mock groups. Tumor growth regression was consistent with changes in reactive oxygen species production and expression of autophagy-related genes. N-acetyl-L-cysteine inhibited changes in the expression of the autophagy-related genes and also suppressed reactive oxygen species production and tumor growth. Hyperthermia + chemotherapy increase expression of autophagy-related genes Beclin1 and LC3B, decrease expression of mammalian target of rapamycin, and concomitantly increase reactive oxygen species generation. These results strongly indicate that mild hyperthermia enhances sensitivity of gastric cancer cells to chemotherapy through reactive oxygen species–induced autophagic death.